大学生对不同华语的语言态度 ：新加坡和来自中国的大学生的态度差异为例 = Singapore university students’ language attitudes towards varieties of Mandarin : a comparison of students from Singapore and China - 叶炜娴 Yap, Wei Xian (2009)
随着―汉语热‖逐渐席卷全球，世界上使用华语的人数越来越多，华语更与英语并列世界五大语言之一。华语和英语的处境相同，使用语言的人分散世界各处，发展出不同的华语。所谓的―native‖（母语）将由谁来定夺，我们要如何看待华语作为中国境外的一种语言？而使用不同种类的华语有什么感受？针对这些问题，此项研究将对40 名新加坡大专生，探讨新加坡学生与中国学生对新加坡华语与中国普通话的不同语言态度。研究使用问卷法，问卷内容包括三个部分：背景调查、听录音以及直接评论方式，让受访者针对不同华语使用者的身份地位（Status）和团结（Solidarity）层面的问题作答。第一部分仔细的收集受访者与不同对象使用的语言，家庭经济状况，以及个人习惯；第二部分让受访者聆听指定录音；第三部分是口音识别能力调查以及直接评论两种华语。结果显示中国人已渐渐接受新加坡华语为标准语，而新加坡学生也并不以中国普通话为至高的标准。这些结果对解决语言与社会问题，如，华语的发展是否以中国为标准还是应该发展本地特色，以及与此相关的语言政策制定等问题都将有所帮助。As “Mandarin fever” sweeps the globe, Mandarin is one of the top world languages that has gained growing importance like English to be an international language. As a result, we are facing the same problem with Chinese as we do with English: How should we regard other kinds of Chinese outside China and how do the speakers feel about them? This study investigates the language attitudes of Singaporean students and students from China towards the spoken Chinese “Huayu” in Singapore and the spoken Chinese “Putonghua” in China. Forty participants who are currently studying in Singapore local universities were recruited for this study. Through three parts of the survey namely, questionnaires, recordings and interviews, the participants answered a series of questions related to the status and solidarity traits of the language. From the findings, we can claim that students from China are gradually accepting the spoken Chinese “Huayu” in Singapore as a standard language and Singapore students do not regard the spoken Chinese “Putonghua” in China as the only standard for Chinese. These results will be helpful for solving certain language and society problems (e.g., whether we should take the spoken Chinese “Putonghua” in China as the only standard or develop “Huayu” as our own trait) as well as for making language policies relating to the issues involved.